The reflection of national ideas in the legacy of I. Nechui-Levytskyi (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
Period of the XIX century is fluently described in the article besides, social and political atmosphere, when on the agenda the questions about the renaissance of the national mentality. Author pays attention on the reflection of national mentality in the Ivan Nechuii-Levitskii`s art and memoirs’ heritage.
Keywords: mentality; writer`s epistoliariy; cultural atmosphere